Correction: Rakhshandeh et al. Protective Effect of Portulaca oleracea on Streptozotocin-Induced Type I Diabetes-Associated Reproductive System Dysfunction and Inflammation. Molecules 2022, 27, 6075 - Hassan Rakhshandeh; Hamed Rajabi Khasevan; Anella Saviano; Mohammad Reza Mahdinezhad; Vafa Baradaran Rahimi; Sajjad Ehtiati; Leila Etemad; Alireza Ebrahimzadeh-bideskan; Francesco Maione; Vahid Reza Askari (Molecules)
In the original publication [...]